Efficiency or Illusion? Reading the 2025 DIPA Block and TKD Reserve from the Perspective of Spending Review and Ibn Khaldun - Miftahurrahmah (UANG: Journal of Fiscal and Monetary Studies, 2025)
Budget efficiency in 2025 has become a key term in Indonesia's fiscal governance as spending space narrows, while the need for public services and priority programs increases. However, efficiency is often debated: is it really spending better or just administrative cuts that risk suppressing productive spending and shifting the burden of adjustment to the regions? This study aims to analyze the design of the 2025 efficiency policy and its implications for spending composition and governance integrity, using a synthesis of the spending review framework and the perspective of Ibn Khaldun (mulk, adl, umran, taraf, fasad). The method used is qualitative with directed qualitative content analysis of policy documents and supporting documents on budgeting and supervision (Presidential Instruction 1/2025, operational provisions for adjustments, and summaries of related documents). The findings show that efficiency is designed as a front-loaded spending control regime through DIPA blocking at ministries/agencies and TKD reserves, with a focus on cutting bureaucratic transaction costs in the regions. This policy has the potential to improve spending discipline, but it also poses the risk of false efficiency if it is not accompanied by program evaluation, protection of basic services, transparency of criteria, and risk-based oversight that prevents wasteful substitution.